A review of the model minority myth: understanding the social, educational and health impacts. Issue 3 (17th February 2023) - Walton, Jessica; Truong, Mandy
ABSTRACT: As shown by the recent increase in anti-Asian racism and violence worldwide, the label of "model minority" is flawed and fails to capture the breadth and depth of the experiences of Asian people. Our paper is the first to provide a scoping review of empirical research (ninety-seven studies) that examine the social, educational and health and wellbeing impacts of the model minority myth (MMM) for people of Asian descent in white-majority countries. Key findings indicate that the MMM is complex and contradictory and is present across multiple sectors. Therefore, the MMM needs to be understood holistically as a structural issue that has implications for reinforcing racial inequities. Future research should adopt multilevel frameworks and methods to further understand community and structural impacts of the MMM on people of Asian descent internationally and consider how the MMM contributes to a white racial grammar that normalizes racial stratification and racist structures.